Hyperprogression in a Patient With Hepatocellular Cancer Treated With Atezolizumab and Bevacizumab: A Case Report and Review of Literature - Balraj Singh MD; Parminder Kaur MD; Michael Maroules MD (SAGE Publishing, 2021)
Immune checkpoint inhibitors have emerged as a novel treatment in a wide variety of malignancies; however, it is associated with a distinctive array of side effects known as immune-related adverse events. Hyperprogression is defined as an accelerated growth of disease burden in patients treated with immunotherapy. Limited literature is available regarding hyperprogression in hepatocellular cancer. We report a case of a 36-year-old male with no past medical history who presented with nausea, vomiting, and abdominal pain and was diagnosed with unresectable hepatocellular cancer and thereby started on atezolizumab and bevacizumab. The patient got only 1 cycle of treatment and unfortunately had hyperprogression of disease.